Teacher's attitudes towards inclusion and the inclusion of students with emotional and behavioural disorders - Anastasiadou, Elisavet (2016)
Inclusion is both a symbolic and a practically meaningful process inextricably inter-twined with equity, social and educational participation. Teachers are a fundamental part of this process. Therefore, their attitudes carry a dynamic, which, in turn can be linked to educational success and inclusive implementation. Students with emotional and behavioural disorders constitute a challenging and vulnerable group of students, often excluded from the educational setting, with severe academic and social consequences. The main objective of the current study was to explore teachers’ attitudes to-wards the inclusion of students with emotional and behavioural disorders, in primary and secondary education. To achieve this aim, it was important to draw on the relationship between teachers’ attitudes towards inclusion in general and towards the inclusion of students with emotional and behavioural disorders. The purpose was also to evaluate which type of emotional and behavioural disorders was more challenging and to select, which element of support was considered to be vital, in meeting the needs of students with emotional and behavioural disorders. A survey using a questionnaire was conducted, so as to collect data from three hundred participants from primary and secondary education respectively, both from rural and urban areas in Greece. The findings indicated that the teachers, who were ready to include students with disabilities and/or learning difficulties in general, were also positive towards stu-dents with emotional and behavioural disorders. Primary school teachers were more positive towards inclusion than secondary teachers. Schizophrenia was the type of emotional and behavioural disorder characterized as most challenging. The school psychologist and collaboration with parents have gathered the majority of the responses. The main idea of the findings supported that previous experience and education comprised fundamental factors, having a direct effect on the teachers’ attitudes and that inclusive implementation requires practical support.